2018
DOI: 10.4049/jimmunol.1800503
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lipoproteins Constitute the TLR2-Stimulating Activity of Serum Amyloid A

Abstract: Studies comparing endogenous and recombinant serum amyloid A (SAA) have generated conflicting data on the proinflammatory function of these proteins. In exploring this discrepancy, we found that in contrast to commercially sourced recombinant human SAA1 (hSAA1) proteins produced in , hSAA1 produced from eukaryotic cells did not promote proinflammatory cytokine production from human or mouse cells, induce Th17 differentiation, or stimulate TLR2. Proteomic analysis of-derived hSAA1 revealed the presence of numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…The belief that the strong inflammatory stimulus for extrahepatic SAA synthesis was due to cytokine release following cellular elements destruction by feverfewinduced attacks of their membrane lipids seems inconsistent because SAA concentrations did not persist high during the 6 day phytopreparation intake but increased considerably only to post infection hour 72time of acute phase response. As the latter is a dynamic homeostatic event aimed at neutralisation of the challenging agent, support of body recovery and normalisation of systemic functions, it could be speculated that increased SAA concentrations were an in vivo effect of feverfew, associated with its antibacterial activity as SAA blocks cellular receptors and thus, the influence of bacteria and their products on them (Burgess et al, 2018). Also, it is an opsonin and retinol-binding protein (Shah et al, 2006;Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The belief that the strong inflammatory stimulus for extrahepatic SAA synthesis was due to cytokine release following cellular elements destruction by feverfewinduced attacks of their membrane lipids seems inconsistent because SAA concentrations did not persist high during the 6 day phytopreparation intake but increased considerably only to post infection hour 72time of acute phase response. As the latter is a dynamic homeostatic event aimed at neutralisation of the challenging agent, support of body recovery and normalisation of systemic functions, it could be speculated that increased SAA concentrations were an in vivo effect of feverfew, associated with its antibacterial activity as SAA blocks cellular receptors and thus, the influence of bacteria and their products on them (Burgess et al, 2018). Also, it is an opsonin and retinol-binding protein (Shah et al, 2006;Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…SAA can interact with lipophilic macromolecules, including bacterial lipoproteins 11 . In addition, SAA has also been reported to be a potent opsonin of Gram-negative bacteria 12 , 13 , an inhibitor of viral entry into cells 14 16 , and a chaperone for retinoic acid (RA) 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The E. coli expression system has been widely used in the production of reagents including proinflammatory cytokines such as TNFα and IL-1β, and there were not previous concerns over bacterial product contamination with these cytokines. Whereas the authors attributed the previously reported NLRP3 inflammasome-activating property of SAA to bacterial lipoprotein contaminants in the E. coli-derived SAA [105], another recent study demonstrated that SAA purified from human samples was able to stimulate NLRP3 inflammasome activation [101]. Taken together, these findings raise the possibility that bacterial contaminants may modify the biological properties of human SAA1 for a potent cytokine-inducing effect.…”
Section: Saa Receptorsmentioning
confidence: 94%
“…Many of the published studies have included controls for LPS contamination, showing that the SAA protein is necessary for the reported biological functions. A recent study has shown that the bacterial contaminants may not be LPS that acts through TLR4 but lipoproteins that activate TLR2 [105]. The study also showed that adding bacterial lipopeptides into mammalian cell-expressed SAA1 protein could restore the cytokine-like activity that otherwise was missing from the SAA1 protein [105].…”
Section: Saa Receptorsmentioning
confidence: 99%
See 1 more Smart Citation